Culture, emotion regulation, and adjustment - Matsumoto, David (2008)
This article reports differences across 23 countries on 2 processes of emotion regulation – reappraisal and suppression. Cultural dimensions were correlated with country means on both and the relationship between them. Cultures that emphasized the maintenance of social order – that is, those that were long-term oriented and valued embeddedness and hierarchy – tended to have higher scores on suppres- sion, and reappraisal and suppression tended to be positively correlated. In contrast, cultures that minimized the maintenance of social order and valued individual Affective Autonomy and Egalitarianism tended to have lower scores on Suppression, and Reappraisal and Suppression tended to be negatively correlated. Moreover, country-level emotion regulation was significantly correlated with country-level indices of both positive and negative adjustment.